Stationary Gaussian entanglement between levitated nanoparticles. (21st December 2020) - Chauhan, Anil Kumar; Černotík, Ondřej; Filip, Radim
Abstract: Coherent scattering of photons is a novel mechanism of optomechanical coupling for optically levitated nanoparticles promising strong, versatile interactions with light and between nanoparticles. We show that it allows efficient deterministic generation of Gaussian entanglement between two particles in separate tweezers. A combination of red- and blue-detuned tweezers brings a mechanical Bogoliubov mode to its ground state. An additional, dispersively coupled cavity mode can reduce noise in the orthogonal mode, resulting in strong entanglement as quantified by the logarithmic negativity and verifiable with the Duan criterion for realistic experimental parameters. Such an important resource for quantum sensing and quantum simulations is pivotal for current experiments and presents an important step towards optomechanics with multiple particles in the quantum regime.